Peningkatan Hasil Belajar Tematik Terpadu Siswa dengan Model Read, Answer, Discuss, Explain, Create di Sekolah Dasar - Nursalim, Wahyu; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research is motivated by student learning outcomes which are still low. This research aims to describe the use of the Read, Answer, Discuss, Explain, Create model to improve student learning outcomes in integrated thematic learning. This research is classroom action research (PTK) and has four stages, namely planning, implementation, observation, and reflection. The subjects are teachers and students. Research data was obtained from the assessment of the Learning Implementation Plan, implementation process, and learning outcomes. Data collection techniques use test and non-test data collection techniques. The research results showed an increase in: a) RPP cycle I with an average of 86.34% (B) and cycle II 95.45% (SB), b) Teacher activity in the implementation of cycle I with an average of 87.49% ( B) and cycle II 96.43% (SB), while student activities in cycle I with an average of 87.49% (B), and cycle II 96.43% (SB), c) Assessment of participant learning outcomes students in cycle I with an average of 73.75 then experienced an increase in cycle II to 90.10. Based on these results, it is concluded that the Read, Answer, Discuss, Explain, Create model can improve student learning outcomes in thematic learning.